3D map distribution of metallic nanoparticles in whole cells using MeV ion microscopy. (10th April 2017) - VASCO, M.S.; ALVES, L.C.; CORREGIDOR, V.; CORREIA, D.; GODINHO, C.P.; SÁ‐CORREIA, I.; BETTIOL, A.; WATT, F.; PINHEIRO, T.
Summary: In this work, a new tool was developed, the MORIA program that readily translates Rutherford backscattering spectrometry (RBS) output data into visual information, creating a display of the distribution of elements in a true three‐dimensional (3D) environment. The program methodology is illustrated with the analysis of yeast Saccharomyces cerevisiae cells, exposed to copper oxide nanoparticles (CuO‐NP) and HeLa cells in the presence of gold nanoparticles (Au‐NP), using different beam species, energies and nuclear microscopy systems. Results demonstrate that for both cell types, the NP internalization can be clearly perceived. The 3D models of the distribution of CuO‐NP in S. cerevisiae cells indicate the nonuniform distribution of NP in the cellular environment and a relevant confinement of CuO‐NP to the cell wall. This suggests the impenetrability of certain cellular organelles or compartments for NP. By contrast, using a high‐resolution ion beam system, discretized agglomerates of Au‐NP were visualized inside the HeLa cell. This is consistent with the mechanism of entry of these NPs in the cellular space by endocytosis enclosed in endosomal vesicles. This approach shows RBS to be a powerful imaging technique assigning to nuclear microscopy unparalleled potential to assess nanoparticle distribution inside the cellular volume.